SELERA MAKAN ANOA GUNUNG (Babalus quarlesi) PADA SISTEM KAFETARIA (Studi Prabudidaya untuk Penangkaran Anoa di Palu, Sulawesi Tengah) - Mph. Basri (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The research aimed to study the appetite of anoa under cafeteria feeding system. The experiment of cafeteria feeding system was used to obtain information related to dry matter (DM) intakes. The results of the study showed that the anoa appetite was higher when the feed were offered for 96 and 124 hours than that for 24, 48, 72 and 144 hours as indicated by dry matter intakes.  The dry matter intakes were 0.37-33.1 and 0.39-33.47 g/kg BW0.75 when the feed was offered for 96 and 124 hours, respectively. Whereas the dry matter intakes were  0.37-31.22, 0.27-29.17, 0.28-28.18 and 0.27-23.85 g/kg BW0.75 after offering the feed for 24, 48, 72 and 144  hours, respectively..